Bio- and magnetostratigraphic correlation of the Miocene primate-bearing site of Castell de Barberà to the earliest Vallesian. Issue 132 (July 2019) - Alba, David M.; Garcés, Miguel; Casanovas-Vilar, Isaac; Robles, Josep M.; Pina, Marta; Moyà-Solà, Salvador; Almécija, Sergio
Abstract: Castell de Barberà, located in the Vallès-Penedès Basin (NE Iberian Peninsula), is one of the few European sites where pliopithecoids ( Barberapithecus ) and hominoids (cf. Dryopithecus ) co-occur. The dating of this Miocene site has proven controversial. A latest Aragonian (MN7+8, ca. 11.88–11.18 Ma) age was long accepted by most authors, despite subsequent reports of hipparionin remains that signaled a Vallesian age. On the latter basis, Castell de Barberà was recently correlated to the early Vallesian (MN9, ca. 11.18–10.3 Ma) on tentative grounds. Uncertainties about the provenance of the Hippotherium material and the lack of magnetostratigraphic data precluded more accurate dating. After decades of inactivity, fieldwork was resumed in 2014–2015 at Castell de Barberà, including the original layer (CB-D) that previously delivered most of the fossils. Here we report magnetostratigraphic results for the original outcrop and another nearby section. Our results indicate that CB-D is located in a normal polarity magnetozone in the middle of a short (∼20 m-thick) stratigraphic section. The composite magnetostratigraphic section (∼50 m) has as many as four to six magnetozones. These multiple reversals, coupled with the in situ recovery of a Hippotherium humerus from CB-D in 2015, make it unlikely that any of the sampled normal polarity magnetozones correlate with the long normal polarity subchron C5n.2n (11.056–9.984 Ma), which is characteristic of the early Vallesian. Our results support instead a correlation of CB-D with C5r.1n (11.188–11.146 Ma), where the Aragonian/Vallesian boundary is situated, and therefore indicate an earliest Vallesian age of ∼11.2 Ma for Castell de Barberà. Our results settle the longstanding debate about the Aragonian vs. Vallesian age of this site, which appears roughly coeval with the Creu de Conill 20 locality (11.18 Ma), where hipparionins are first recorded in the Vallès-Penedès Basin.